Analisis Kebutuhan Tulangan Kolom dan Balok pada Tribun Penonton Stadion Mini Pancing Provinsi Sumatera Utara - Ailing, Resolina; Qarinur, Muhammad (JURNAL TEKNIK SIPIL CENDEKIA (JTSC), 2024)
Analysis of reinforcement requirements for column and beam work is important to anticipate the lack and excess of reinforcement that will be planned. In this study, the analysis of reinforcement requirements was carried out at the Pancing Mini Stadium in North Sumatra Province. In optimizing the use of reinforcing iron, a method is used, one of method that recently used is Bar Bending Schedule (BBS). BBS is a method that lists a model of reinforcing iron cutting patterns that serves to control the use of reinforcing iron and minimize the remaining material with Microsoft Excel applications. The result of analysis of the volume of reinforcement requirements on columns and beams using conventional connections is 54,830.96 kg, while the result of analysis of the volume of reinforcement requirements on columns and beams using coupler connections is 53,523.57 kg. The comparison result of the volume of reinforcement requirements on columns and beams using conventional connections with coupler connections is 2.3%. The result of the calculation of the cost of reinforcement requirements for columns and beams using conventional connections is IDR743.507.817,60 while the coupler connection is IDR725,688,195.00. Therefore, it can be concluded that the coupler connection is more efficient than the conventional connection in terms of cost.